STUDY OF ANTI-OXIDANT ACTIVITY TEST ON NATURAL MATERIALS USING 1,1-DIFENYL-2-PIKRILHIDRAZIL (DPPH) - Syukri Arief; Risma Sari; Novesar Jamarun; Sumaryati Syukur (Politeknik ATI Padang, 2019)
This study aims to determine the anti-oxidant potential found in natural materials. The antioxidant activity test was carried out on several natural ingredients or common plants that have been known and used for generations by the people of Indonesia. Antioxidant activity testing was carried out using DPPH method using IC50 parameters and natural material samples used were virgin coconut oil from coconut plants, Tanjung leaves and bay leaves. Antioxidant activity test showed that the sample of natural materials used had strong antioxidant activity, it was found that IC50 values were between 50-100 ppm.